تعليم الصبيان في الغرب الاسلامي من القرن3ه/9م إلى9ه/15م - رجاء بكوش; نرجس فرحات حميدة (University of Eloued جامعة الوادي, 2025)
"تناولت هذه المذكرة بالدراسة والتحليل موضوع تعليم الصبيان في الغرب الإسلامي، مبرزةً دوره الأساسي في بناء الفرد والمجتمع في إطار إسلامي متوازن. انطلقت من تحديد المفاهيم الأساسية كالتعليم والصبيان، موضحةً أن التعليم لم يكن مجرد تلقين بل وسيلة لتنشئة أخلاقية وروحية. كما تناولت السياق التاريخي الذي تطور فيه هذا التعليم، خاصة في ظل الفتوحات الإسلامية، وركزت على إسهامات علماء بارزين مثل ابن سحنون والقابسي وابن خلدون، الذين أثروا الفكر التربوي بآرائهم ومؤلفاتهم. ركّزت المذكرة على مؤسسة الكتّاب باعتبارها المدرسة الأولى للطفل، إلى جانب أماكن تعليمية أخرى كالزوايا والربط، مشيرة إلى تنوع فضاءات التعليم في تلك المرحلة. كما تناولت مكانة المعلم وأدواره، ونظام الأجرة، وأهمية العلاقة التربوية بينه وبين الصبي. وقد عُرض نظام التعليم من حيث تقسيم الوقت، والعقوبات، والمقررات التي شملت القرآن، واللغة، والفقه، والعقيدة. وفي الختام، خلصت الدراسة إلى أن تعليم الصبيان كان منظومة متكاملة تهدف إلى إعداد جيل صالح قادر على التفاعل مع محيطه الديني والإجتماعي والثقافي "This thesis studied and analyzed the topic of boys’ education in the Islamic West, emphasizing its essential role in shaping both the individual and society within a balanced Islamic framework. It began by defining key concepts such as ""education"" and ""boys,"" showing that education was not mere instruction but a means of spiritual and moral upbringing. The historical context of this educational development was examined, particularly after the Islamic conquests, with a focus on contributions by key scholars such as Ibn Sahnun, Al-Qabisi, and Ibn Khaldun, who enriched educational thought through their writings. The study highlighted the kuttab as the primary institution for children’s early education, alongside other venues like zawiyas and ribats, reflecting the diversity of learning spaces at the time. It also explored the teacher’s role, social status, compensation system, and his educational relationship with students. The structure of education was discussed in terms of time organization, discipline, and curriculum, which included the Qur’an, Arabic language, jurisprudence, and creed. In conclusion, the thesis found that boys’ education formed an integrated system aimed at preparing a righteous generation capable of engaging positively with its religious, social, and cultural environment. "
مذكرة ماستر تخصص تاريخ الغرب الإسلامي
Keywords: الصبيان; الكتاتيب; التعليم; الغرب الإسلامي; Boys; education; Islamic West; Kuttabs